(untitled) (Research, Society and Development, 2021)
Hyperuricemia is commonly seen in patients with metabolic syndrome (MS) and both are related to the risk of developing cardiovascular disease. Thus, the present study aims to verify whether there is an association between hyperuricemia and MS related factors in a mixed population in the city of Salvador, Bahia, Brazil. Method: Cross-sectional study with 610 patients, adults and elderly, of both sexes, with MS and attended at a nutrition school clinic between the years 2013-2018. To analyze the results, a descriptive assessment of sociodemographic data, Pearson’s Chi-Square test and Fisher’s exact test were performed. Results were considered significant p≤ 0.05. Results: The prevalence of hyperuricemia was 14% (n=79). There was an association between hyperuricemia and hypertension (p=0.035) and hyperuricemia and hypertriglyceridemia (p=0.002), but there was no significant association between hyperuricemia and hyperglycemia (p= 0.56) and low concentration of high density lipoprotein (p=0. 90), as well as body mass index (p=0.165) and C-reactive protein (p=0.801). Conclusion: There was a significant association between hyperuricemia and metabolic syndrome cofactors.